2003
DOI: 10.1063/1.1564818
|View full text |Cite
|
Sign up to set email alerts
|

Henry’s Constants and Vapor–Liquid Distribution Constants for Gaseous Solutes in H2O and D2O at High Temperatures

Abstract: We have developed correlations for the Henry's constant k H and the vapor-liquid distribution constant K D for 14 solutes in H 2 O and seven solutes in D 2 O. The solutes considered are common gases that might be encountered in geochemistry or the power industry. Solubility data from the literature were critically assessed and reduced to the appropriate thermodynamic quantities, making use of corrections for nonideality in the vapor and liquid phases as best they could be computed. While the correlations prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
147
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(164 citation statements)
references
References 2 publications
7
147
0
10
Order By: Relevance
“…Crovetto 32 also developed an equation valid from 100 C to the critical point of water. This equation corresponds well with the equation of Fernández-Prini et al 36 to within a few percent (except at the critical point), whereas the other correlations typically deviate 10% or more in the high-temperature range.…”
Section: Thermodynamic Datasupporting
confidence: 66%
See 3 more Smart Citations
“…Crovetto 32 also developed an equation valid from 100 C to the critical point of water. This equation corresponds well with the equation of Fernández-Prini et al 36 to within a few percent (except at the critical point), whereas the other correlations typically deviate 10% or more in the high-temperature range.…”
Section: Thermodynamic Datasupporting
confidence: 66%
“…Critical reviews of the solubility of CO 2 have been made by Crovetto 32 and by Carroll et al 33 Compilations are available from Scharlin et al 34 De Visscher and Vanderdeelen 18 found that the evaluation of Crovetto 32 at 0-80 C is more consistent with the thermodynamic data of CODATA 35 than the evaluation of Carroll et al 33 Thermodynamic properties derived from different models are given in Table 1. A more recent review of CO 2 solubility data is by Fernández-Prini et al 36 However, their correlation has poor consistency with CODATA. 35 From the above studies, the equation of Crovetto 32 is the most appealing one because of its higher consistency with CODATA, and because it is based on a large data set.…”
Section: Thermodynamic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The Henry's coefficient can be found in the literature, using the compilation of Sander or specific articles [36][37][38][39][40][41]. When the value cannot be found for a specific compound or in specific conditions, it remains possible to use some thermodynamic models which provide good accuracies [39,[42][43][44][45].…”
Section: Mass Transfer Ratementioning
confidence: 99%